Analisis Isi Pesan Dakwah Bilal_Tatobat Pada Media Instagram Edisi Minggu Pertama Januari 2026 - Dhea Aftariza; Ahmad Sampurna (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2026)
This study aims to examine the characteristics of Islamic messages delivered by the influencer bilal_tatobat, who is widely recognized because his body is covered with tattoos. This qualitative study employed in-depth interviews conducted through WhatsApp and analyzed strategies for delivering Islamic messages on Instagram using the Hypodermic Needle Theory. The findings indicate that physical appearance, often considered an important factor by communicants, does not hinder bilal_tatobat in disseminating Islamic teachings through social media. Instead, his distinctive appearance attracts attention and increases audience engagement with the religious content he shares. The study also reveals that his messages are particularly appealing to male audiences and mothers whose children are involved in negative social environments. This research provides insights for communicators in developing effective strategies for delivering Islamic messages through Instagram and demonstrates that religious content can simultaneously serve educational purposes and create economic opportunities for content creators in contemporary digital society. The findings contribute to understanding contemporary patterns of digital da'wah communication.